Class XI Students' Perceptions of Swimming Learning at Darussalam Vocational School Karangpucung in 2022/2023 - Ari Gana Yulianto; Kusmiyati Kusmiyati; Joni Purwanto (Universitas Sebelas Maret, 2023)
This research aims to find out how high the perception of class X students is in participating in swimming lessons at Darussalam Karangpucung Vocational School. This research method is quantitative descriptive research with surveys. The research subjects were all class XI students at Darussalam Vocational School, Karangpucung, totaling 284 students. Then samples were taken using proportional random sampling techniques as many as 157 students. The instrument used was a questionnaire with instrument reliability of 0.841. The data analysis technique used was descriptive statistical percentages. The results of the research show that the students' perception of participating in class XI swimming lessons at Darussalam Vocational School Karangpucung is very positive. The highest frequency consideration was 123 respondents or 78.3%, then 30 respondents or 19.1% had a positive perception, while 4 respondents or 2.5% had a less positive perception and no respondents had a negative perception or 0%.